Construção de modelos didáticos táteis para o ensino de biologia: uma pesquisa participante em Santarém-Pa - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
This participatory research aimed to reflect on the activities that took place during the period between August and December 2022 in order to collaboratively promote the construction of tactile didactic models for the teaching of biology. The work took place jointly with UEES (Specialized Educational Unit) of SEDUC (Department of Education of the State of Pará) in Santarém and the Accessibility Nucleus of the Federal University of Western Pará (UFOPA) with the aim of covering teachers and educators who work in mainstream education and instigate the promotion of inclusive teaching/learning. A workshop was offered for professors and students in the degree area, and during the workshop, participants developed tactile didactic models for teaching biology and, at the end of the project, they presented their work, followed by an evaluation made by people with blindness for greater contributions and suggestions. With the workshop it was noticed that the participants could learn about the production of tactile didactic models in a practical way and at low cost, which resulted in a significant contribution of this research to the professional experience of the participants.
Keywords: Inclusão; Tátil; Deficiência Visual; Oficina; CNPQ:: CIÊNCIAS BIOLÓGICAS